DETERMINANTS OF FINANCIAL PERFORMANCE IN ISLAMIC AND CONVENTIONAL BANKS: THE MEDIATING ROLE OF OPERATING EFFICIENCY AND THE MODERATING EFFECT OF SHARIA COMPLIANCE (Contemporary Journal of Social Science Review, 2025)
The banking sector plays a pivotal role in economic development, financial stability, and resource allocation, particularly in emerging economies where banks dominate the financial system. This study examines the determinants of financial performance in Islamic and conventional banks operating in Pakistan by explicitly incorporating the mediating role of operating efficiency and the moderating influence of Sharia compliance. Drawing on banking efficiency theory, the structure–conduct–performance paradigm, and Islamic financial intermediation theory, the study develops a comprehensive conceptual framework and empirically tests it using structural equation modelling. Financial performance is conceptualized as a multidimensional construct measured through profitability and risk-adjusted indicators, while deposits, reserves, overhead expenses, and market concentration are treated as key bank-specific determinants. Using panel data from Pakistani banks, the findings reveal that deposits and reserves exert a positive and significant influence on financial performance, whereas overhead expenses negatively affect performance. Operating efficiency partially mediates these relationships, highlighting its role as a critical internal transmission mechanism. Moreover, multi-group analysis indicates that Sharia compliance significantly moderates the efficiency performance relationship, suggesting that institutional and religious constraints reshape performance dynamics. The study contributes to the banking literature by integrating mediation and moderation within a unified framework and offers important implications for bank managers, regulators, and policymakers in dual banking systems.